The Effect of Net Interest Margin (NIM) and Operational Costs Operating Income (BOPO) on Return on Assets (RoA) at PT. Bank Rakyat Indonesia, Tbk - Eni Puji Astuti; Farah Maulia Husna (Universitas Negeri Makassar, 2020)
Banks are known as financial institutions whose main activities are collecting funds from the public, channeling funds to the public, and performing other services in the banking sector. The purpose of this study was to determine the effect of Net Interest Margin (NIM) and Operational Income Operating Costs (BOPO) Against Return On Assets (ROA). The sample of this study is the financial statements of PT. Bank Rakyat Indonesia (Persero) Tbk. from 2008 to 2017, this research uses the Multiple Linear Regression Analysis method using an SPSS test. The results showed that Net Interest Margin has a positive effect on Return On Assets, with a tcount greater than ttable (3.021> 2.365) and a significance level of 0.019 less than a significant level of 0.05 (0.019 <0.05) and Operating Income Costs Operations have a negative effect on Return On Assets, with a tcount greater than ttable (-7,166> 2,365) and a significance level of 0,000 less than a significant level of 0.05 (0,000 <0.05). Net Interest Margin (NIM) and Operational Costs Operating Income (BOPO) has a positive effect on Return On Assets (ROA), with a Fcount greater than Ftable (26.298> 4.46) and a significance level of 0.001 smaller than a significant level of 0, 05 (0.001 <0.05). The coefficient of determination that can be equal to 0.849 or 84.9% means as much as 15.1% is likely influenced by variables not examined.